Manajemen SDM dalam Pendidikan Islam: Studi Kasus SDIT Insantama Leuwiliang - Rusdiono Mukri; Maemunah Sa’diyah (LPPM Institut Nasional Laa Roiba Bogor, 2021)
This study aims to determine the implementation of integrated quality management (total quality management /TQM), especially in human resource management (HR) in Islamic education at SDIT Insantama Leuwiliang, Bogor. The research used descriptive qualitative method which was carried out by collecting data obtained from documentation, observation and interviews. The results show that SDIT, which was founded in 2011, always meets the needs of educators and education personnel according to needs such as administrative, cleaning service, and security personnel. HR competencies are enhanced through education and training, seminars, workshops and internships. Recruitment and selection of HR candidates is carried out every year since its establishment, in line with the development of the school and the increase in the number of students. Meanwhile, compensation, both financial and non-financial, is constantly being improved in order to provide qualified human resources. The results also show that the implementation of Islamic Education TQM at SDIT Insantama Leuwiliang has been implemented well, especially in the field of HR management, starting from HR planning, recruitment, selection of HR candidates, training and development, to employee relations.